In vitro stimulation of MC3T3-E1cells and sustained drug delivery by a hierarchical nanostructured SiO2-CaO-P2O5 scaffold - Ramiro-Gutiérrez, María Lourdes; Santos-Ruiz, Leonor; Borrego-González, Sara; Becerra-Ratia, José; Díaz-Cuenca, Aránzazu (Elsevier, 2016)
A hierarchical scaffold, SP1_h_HA, consisting of a biomimetic nano-hydroxyapatite surface coating growth onto a reticulated structure having a nano-organized porous texture was fabricated and functionally studied in vitro using osteoprogenitor cells. Three scaffold materials (designated as SP0-l, SP0-h and SP1-h) were also prepared through modifications of the processing variables as control materials. The scaffolds were characterized showing well-interconnected micron-sized voids and a nano (4-6 nm)-organized porosity. In order to evaluate potential local risks and performance over mammalian cells the scaffolds were studied in comparison with a commercial clinical grade scaffold material, ProOsteon® 500R. MC3T3-E1 pre-osteoblast viability was evaluated using the resazurin assay and field emission gun scanning electron microscopy (FEG-SEM), showing in all cases good proliferative response. Alkaline phosphatase (ALP) production and analysis of the differentiation marker osteocalcin (OC), both in non-osteoinductive and osteoinductive media, were assessed using colorimetric and RT-PCR methods. The implementation of the new scaffold processing variables enhanced ALP activity with respect to the SP0-l control material. The cell proliferation, ALP activity, and mRNA OC expression response to SP1_h_HA scaffold were higher than those observed after the use of ProOsteon® 500R. In addition, SP1_h_HA scaffold showed a two stage sustained release of gentamicin sulfate (GS) instead of the quick release shown by ProOsteon® 500R. These results suggest that our synthesized scaffold could be effective for antibiotic delivery and bone regeneration and a better option than ProOsteon® 500R
Keywords: Regulación celular; Células - Diferenciación; Nanotecnología; Tejidos (Biología) - Cultivo; Mesoporous bioactive glass; SBA-15; ProOsteon (R); Osteoprogenitor cells differentiation; Gentamicin; Drug release